Secure Location Privacy Transmitting Information on Cellular Networks - Nema, Bashar M.; Mohammed, Shatha J. (Iraqi Journal of Science, 2022)
As smartphones incorporate location data, there is a growing concern about location  privacy as smartphone technologies advance. Using a remote server, the mobile applications are able to capture the current location coordinates at any time and store them. The client awards authorization to an outsider. The outsider can gain admittance to area information on the worker by JSON Web Token (JWT). Protection is giving cover to clients, access control, and secure information stockpiling. Encryption guarantees the security of the location area on the remote server using the Rivest Shamir Adleman (RSA) algorithm. This paper introduced two utilizations of cell phones (tokens, and location). The principal application can give area information by means of the geographic position method of these gadgets. Every cell phone can create a token. The token holds secret keys got from versatile fixed identifiers for the most part of the Social Security Number (SSN) for each SIM (Endorser Personality Module) Chronic Number) and IMEI (Global Portable Hardware Character) by RSA calculation. The token is going through the short and informative administration of Short Message Service (SMS) from the client to the outsider. Information is scrambled before being stored on a faraway worker. The actual worker can't comprehend the area’s information. The third-party cannot follow the area if the client utilizes distinctive mystery keys. The client’s data and area information are saved by the various workers. The proposed application offers a mysterious sharing instrument that uses token verification to grant clients access to scrambled area data and provides encryption data in a remote server with an authentication token, achieving mutual authentication on each mobile device and user concealment.